Enterprise architecture based on TOGAF for the aof educational institutions to e-learning using the DLPCA Methodology and Google Classroom - Puntillo, Geraldine (2022)
Given the current situation of online classes, it is necessary to implement a Business Architecture model in order to facilitate the adaptation of virtual teaching, since 97.4% of teachers give up the use of information systems for learning. In addition, up to 80% of students experience stress with this new modality of learning. Based on this context, we can identify the gap in the adaptation to the virtual class process as a latent problem. Therefore, a model composed of 3 stages (Analysis, design, and validation) is proposed. Stage 1 includes the analysis of components on which the model will be developed. Stage 2 describes the Open Group Architecture Framework (TOGAF) on which the model will be developed, and the Discover, Learn, Practice, Collaborate, and Assignment (DLPCA) e-learning Methodology as the basis of the business process to be proposed. Finally, in stage 3, the model was validated in a private school in Lima with 70 students, 2 teachers, and 1 director, where it was shown that our proposal increased user satisfaction by 18.97%, positively increased adaptation to virtual classes by 28.50%, and also obtained a 75.34% acceptance of our proposal by the subjects of study, which shows the effectiveness of our solution to the problem.